Comparative Genomic and Transcriptomic Analysis Reveals Specific Features of Gene Regulation in Kluyveromyces marxianus - Yu, Yao; Mo, Wenjuan; Ren, Haiyan; Yang, Xianmei; Lu, Wanlin; Luo, Tongyu; Zeng, Junyuan; Zhou, Jungang; Qi, Ji; Lu, Hong (Frontiers in Microbiology, 2021)
K. marxianus is a promising host for producing bioethanol and heterologous proteins. It displays many superior traits to a conventional industrial yeast species, Saccharomyces cerevisiae, including fast growth, thermotolerance and the capacity to assimilate a wider variety of sugars. However, little is known about the mechanisms underlying the fast-growing feature of K. marxianus. In this study, we performed a comparative genomic analysis between K. marxianus and other Saccharomycetaceae species. Genes involved in flocculation, iron transport, and biotin biosynthesis have particularly high copies in K. marxianus. In addition, 60 K. marxianus specific genes were identified, 45% of which were upregulated during cultivation in rich medium and these genes may participate in glucose transport and mitochondrion related functions. Furthermore, the transcriptomic analysis revealed that under aerobic condition, normalized levels of genes participating in TCA cycles, respiration chain and ATP biosynthesis in the lag phase were higher in K. marxianus than those in S. cerevisiae. Levels of highly-copied genes, genes involved in the respiratory chain and mitochondrion assembly, were upregulated in K. marxinaus, but not in S. cerevisiae, in later time points during cultivation compared with those in the lag phase. Notably, during the fast-growing phase, genes involved in the respiratory chain, ATP synthesis and glucose transport were co-upregulated in K. marxianus. A few shared motifs in upstream sequences of relevant genes might result in the co-upregulation. Specific features in the co-regulations of gene expressions might contribute to the fast-growing phenotype of K. marxianus. Our study underscores the importance of genome-wide rewiring of the transcriptional network during evolution.